HIV infection and AIDS reported cases in two municipalities near Lisbon between 2015 and 2019. (30th September 2020) - Cunha, I; Lopes, D; Bragança Pereira, M; Duarte, S; Moreira, A; Abreu Gomes, F; Machado Gil, M; Esteves, H
Abstract: Background: In the WHO European Region, in 2018, there were 16.2 newly diagnosed HIV infections per 100, 000. In Portugal, there were 9.5 new cases per 100, 000 population. The aim of this study is to analyse HIV/AIDS's notifications in the group of primary healthcare centres of Loures-Odivelas (ACES LO), with 340, 000 inhabitants, between 2015 and 2019. Methods: An observational, descriptive, retrospective, quantitative study was performed. Data was collected in March 2020, from the National System of Epidemiological Surveillance Database. Variables included were age, sex, HIV's presentation, country of probable origin of infection, probable form of transmission, partner characteristics, pregnancy at diagnosis, reason for testing/consultation, anti-retroviral therapy (ART) before diagnostic of AIDS. Descriptive analysis was performed for all variables. Results: In ACES LO, there were 83 notified cases of HIV infection/AIDS between 2015 and 2019, with 36.1% of cases notified in 2019. The male to female ratio was 1.4. The average age was 41.7 years old. At time of notification, 56.6% of cases were asymptomatic and 25.3% had clinical criteria for AIDS. Guinea-Bissau was the probable origin of infection in 43.0% of cases (n = 23). Men having sex with men (MSM) was the probable form of transmission in 19.3% of cases. In 19.6% of cases of heterosexual contact, the partner was known to have HIV infection. Six women were pregnant at time of diagnosis. Testing was done on a routine basis in 22.2% of cases (n = 54). Among those with clinical criteria for AIDS (n = 21), 5 cases had previously taken ART. Conclusions: There was an increase in notified cases of HIV infection/AIDS from 2015 to 2019 in ACES LO. The male to female ratio was lower than for Portugal in 2018.The proportion of cases with AIDS at time of notification was higher than for Portugal in 2018. Preventive strategies should be reinforced for people with partners diagnosed with HIV infection and perhaps for people. Key messages: More than one third of cases were notified in 2019. Preventive strategies should be reinforced for people with partners diagnosed with HIV infection.